(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim here is to discuss some important concepts about rational numbers like the algebraic properties of rational numbers, the order properties of rational numbers, the density property of rational numbers along with the geometrical representation of rational numbers.